Involvement of Cholinergic and Adrenergic Drugs Mechanisms in Stomach Reactions (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The work is devoted to the study of serotonergic structures that enhance gastricmotility. Experiments were performed on2-4 rats in the surgical stage of anesthesia, mechanical ventilation, bilateral vagotomy and bilateral cutting of the lingual pharyngeal nerves. The mechanical activity of the stomach was recorded in response to the administration of serotonin adipinate in intact animals and against the background of the continued action of adreno-and holinoblockers. It was found that the blockade of adreno-and holinoreceptors not only does not prevent, but on the contrary, promotes the manifestation of stomach reactions to serotonin, and the blockade of beta-adrenoreceptors increased the severity of gastric stimulant effects by almost 90%. It was concluded that adrenergic and cholinergic mechanisms prevent the manifestation of stimulatory reactions of serotonin-reactive structures on gastric motility.